POLICY IMPLEMENTATION RURAL INFRASTRUCTURE DEVELOPMENT PROGRAM (PPIP) IN LOPANA VILLAGE, NORTH SULAWESI PROVINCE - Kurniati, Poni Sukaesih; Sitorus, David Natanael (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The goal of this study is to learn about the rural infrastructure development program (PPIP) policy execution in Lapona Village, a sub-district of Amurang Timur, South Minahasa Regency, North Sulawesi Province. The descriptive methodology was adopted in this research, with data gathering strategies carried out through literature studies. The findings revealed that the execution of the rural infrastructure development program (PPIP) policy in Lapona Satu Village was based on communication, resources, dispositions, and bureaucratic structure. The impact of this research is to learn about the Rural Infrastructure Program Policy (PPIP) implementation in Lapona Village and to be able to re-examine this research in order to obtain more relevant results